Hydrophobic catalyst and preparation method thereof

By forming a metal oxide sol composite support on the porous styrene-divinylbenzene copolymer SDB, and then supporting the active metal to control its grain size, the waste of active metal caused by the large grain size of active metal in existing hydrophobic catalysts is solved, and the utilization rate of catalytic activity and active metal are improved.

CN119819379APending Publication Date: 2025-04-15CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411918712.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Among the existing hydrophobic catalysts of porous styrene-divinylbenzene copolymer-supported active metals, the grain size of the active metal is large, which makes it impossible for the grains to fully participate in the reaction, resulting in waste of active metals, and the catalytic activity still needs to be improved.

Method used

By attaching the sol of the metal oxide to the SDB and then drying it, a composite support is formed, and then the active metal is supported on the composite support, and the average particle size of the active metal grains is controlled to be less than or equal to 4 nm, preferably 2 nm to 3 nm, so as to improve the dispersion and catalytic activity of the active metal.

Benefits of technology

The higher dispersion of the active metal and the increase of catalytic active sites are achieved, and the catalytic activity of the hydrophobic catalyst and the utilization rate of the active metal are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819379A_ABST
    Figure CN119819379A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophobic catalyst and a preparation method thereof. The hydrophobic catalyst comprises a porous styrene-divinyl benzene copolymer (SDB) and active metal distributed on at least part of the surface of the pore wall of the SDB, the active metal is selected from one or more of platinum, palladium, ruthenium and rhodium, and the average particle size of crystal grains of the active metal is smaller than or equal to 4 nm. The hydrophobic catalyst has improved active metal dispersibility and catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hydrophobic catalysts, and in particular to a hydrophobic catalyst using a porous styrene-divinylbenzene copolymer as a carrier and a preparation method thereof. Background Art

[0002] Porous styrene-divinylbenzene copolymer (SDB) loaded active metal hydrophobic catalyst (such as Pt-loaded SDB) is a hydrophobic catalyst mainly used in heavy water upgrading, tritium-containing wastewater volume reduction, heavy water production, ultra-light water production, hydrogenation and oxidation of organic matter, etc. It is a key material for realizing liquid-phase catalytic exchange reaction of water hydrogen isotopes.

[0003] The particle size of the active metal crystals in the above hydrophobic catalyst is relatively large, and the interior of the crystals cannot fully participate in the reaction, resulting in a waste of active metals, and the catalytic activity still needs to be improved. Therefore, it is necessary to provide an improved hydrophobic catalyst. Summary of the invention

[0004] In view of this, the main purpose of the present disclosure is to provide a hydrophobic catalyst and a preparation method thereof. The hydrophobic catalyst has improved dispersibility of active metals and catalytic activity.

[0005] In order to achieve the above objectives, the present disclosure provides the following technical solutions.

[0006] The first aspect of the present disclosure provides a hydrophobic catalyst, comprising a porous styrene-divinylbenzene copolymer SDB and an active metal distributed on at least a portion of the surface of the pore wall of the SDB, wherein the active metal is selected from one or more of platinum, palladium, ruthenium, and rhodium, and the average particle size of the active metal crystal grains is less than or equal to 4 nm. In the above hydrophobic catalyst based on SDB, the active metal crystal grains have a reduced average particle size, so that the active metal can provide more catalytic active sites, thereby improving the catalytic activity of the catalyst.

[0007] According to an embodiment of the present disclosure, the average particle size of the active metal crystal particles is 2 nm to 3 nm, which is more conducive to improving the utilization rate of the active metal by increasing the dispersibility of the active metal and increasing the activation sites.

[0008] According to an embodiment of the present disclosure, the mass percentage of the active metal relative to the mass of the hydrophobic catalyst is 0.5% to 1.5%, which is more conducive to increasing the active metal loading and activation sites, thereby improving the utilization rate of the active metal.

[0009] According to one embodiment of the present disclosure, the hydrophobic catalyst also includes a metal oxide distributed on at least a portion of the surface of the SDB pore wall, wherein the metal oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cobalt oxide, iron oxide, nickel oxide, and cerium oxide.

[0010] According to one embodiment of the present disclosure, the mass percentage of the metal oxide is 0.2% to 0.7% relative to the mass of the hydrophobic catalyst.

[0011] The second aspect of the present disclosure provides a method for preparing a hydrophobic catalyst according to any of the above embodiments, the hydrophobic catalyst includes a porous styrene-divinylbenzene copolymer SDB and an active metal distributed on at least part of the surface of the SDB pore wall, the average particle size of the active metal crystals in the hydrophobic catalyst is less than or equal to 4nm, preferably 2nm to 3nm, wherein the method includes: by attaching a sol of a metal oxide to the SDB and then drying, the metal oxide is loaded on the SDB to obtain a composite carrier; and the active metal is loaded on the composite carrier to obtain the hydrophobic catalyst, wherein the active metal is selected from one or more of platinum, palladium, ruthenium, and rhodium; the metal oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cobalt oxide, iron oxide, nickel oxide, and cerium oxide. The present application first loads the metal oxide on the surface of the pores of the SDB through a sol, and when the active metal is subsequently loaded, the migration and aggregation of the active metal are inhibited through metal interaction, thereby facilitating the dispersibility of the active metal subsequently loaded, increasing the active sites, and improving the catalytic exchange efficiency of the catalyst.

[0012] According to an embodiment of the present disclosure, in the sol, the content of the metal oxide is 0.5% to 1.5% by mass, which is conducive to the stability of the sol, thereby improving the dispersibility of the metal oxide in the composite carrier.

[0013] According to an embodiment of the present disclosure, the drying temperature is 50° C. to 70° C. This is conducive to more stably attaching the metal oxide sol to the SDB.

[0014] According to one embodiment of the present disclosure, the mass ratio of the composite carrier to the SDB is (1.02-1.08):1.

[0015] According to an embodiment of the present disclosure, the SDB includes one or more of the following features:

[0016] (1) The BET specific surface area of ​​the SDB is 35 m 2 / g to 45m 2 / g,

[0017] (2) The average pore size of the SDB is 140 nm to 180 nm,

[0018] (3) The pore volume of the SDB is 1.4 cm 3 / g to 1.8cm 3 / g.

[0019] According to one embodiment of the present disclosure, the active metal is loaded onto the composite carrier, including: the composite carrier is impregnated with a solution containing ions of the active metal element and then dried to obtain a reduction precursor; and the reduction precursor is subjected to a reduction treatment to obtain the hydrophobic catalyst, wherein the reduction treatment includes reducing the reduction precursor in an atmosphere containing a reducing gas. By impregnation with the above solution, a uniform solution containing ions of the active metal element is utilized to improve the dispersibility of the active metal. Through the above reduction process, it is beneficial to fully reduce the salt of the active metal.

[0020] According to an embodiment of the present disclosure, the solvent of the solution is selected from one or more of ethanol, methanol, water, and ethylene glycol, thereby facilitating the solution to diffuse smoothly into the interior of the carrier.

[0021] According to one embodiment of the present disclosure, the content of active metal elements in the solution is 1 g / L to 5 g / L, which is conducive to more uniform dispersion of active components on the carrier.

[0022] According to an embodiment of the present disclosure, the reducing gas is hydrogen, and the reduction temperature is 280° C. to 320° C. This is conducive to the full reduction of the active components.

[0023] According to one embodiment of the present disclosure, after the active metal is loaded onto the composite support, the preparation method further comprises etching at least a portion of the metal oxide with an alkaline solution. The active metal and SDB are stable relative to the alkaline solution, and the alkaline solution selectively etches and removes a portion of the metal oxide, thereby increasing the exposed area of ​​the SDB and improving the hydrophobicity, thereby improving the catalytic exchange efficiency of the hydrophobic catalyst.

[0024] According to an embodiment of the present disclosure, the alkali in the alkaline solution is selected from one or more of NaOH, KOH, and ammonia water, thereby being conducive to etching away most of the metal oxides while avoiding damage to the active metals that have been loaded.

[0025] According to one embodiment of the present disclosure, the mass percentage of alkali in the alkali solution is 1 wt % to 3 wt %.

[0026] According to one embodiment of the present disclosure, the solvent of the alkaline solution is selected from one or more of ethanol, methanol, and ethylene glycol.

[0027] According to one embodiment of the present disclosure, the ratio of the volume of the alkaline solution to the mass of the hydrophobic catalyst is 3.5 mL / g to 4.5 mL / g, which is conducive to fully etching the metal oxide.

[0028] According to an embodiment of the present disclosure, the etching time is 0.5 h to 1.5 h, which is more conducive to fully etching the metal oxide without affecting the active metal content.

[0029] The hydrophobic catalyst disclosed in the present invention is based on SDB, wherein the active metal crystal particles have a reduced average particle size, so that the active metal can provide more catalytic active sites, thereby improving the catalytic activity of the catalyst. In the preparation method disclosed in the present invention, the metal oxide is first loaded onto the surface of the pores of the SDB through a sol, so that when the active metal is subsequently loaded, the migration and aggregation of the active metal are inhibited through metal interaction, which is conducive to improving the dispersibility of the active metal, obtaining active metal crystal particles with a reduced average particle size, thereby providing more catalytic sites at the same loading amount.

[0030] In addition to the technical problems solved by the present disclosure, the technical features that constitute the technical solutions, and the beneficial effects brought about by the technical features of the technical solutions described above, other technical problems that can be solved by the present disclosure, other technical features included in the technical solutions, and the beneficial effects brought about by these technical features will be further described in detail in the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 The transmission electron microscopy image of the hydrophobic catalyst prepared in Example 1 is shown.

[0033] Figure 2 The transmission electron microscopy image of the hydrophobic catalyst prepared in Example 2 is shown.

[0034] Figure 3 The transmission electron microscope image of the hydrophobic catalyst prepared in Comparative Example 1 is shown. DETAILED DESCRIPTION

[0035] The technical solution of the present disclosure will be clearly and completely described below in conjunction with specific implementations and drawings. Obviously, the described implementations are only part of the implementations of the present disclosure, not all of the implementations. Based on the implementations in the present disclosure, all other implementations obtained by ordinary technicians in the field without creative work are within the scope of protection of this application.

[0036] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. In the event of a conflict, this specification takes precedence.

[0037] It should be noted that in the present disclosure, the term "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "comprising..." does not exclude the presence of other related elements in the method or device including the element.

[0038] Except in any operating examples, or where otherwise indicated, all numerals used in the specification and claims indicating component amounts, reaction conditions, etc. should be understood to be modified by the term "approximately" in all cases. Unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximate values, which can vary according to the desired properties to be obtained by the present disclosure. Although the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximate values, the numerical values ​​set forth in the specific embodiments are reported as accurately as possible.

[0039] The above steps are divided only for clear description. When implemented, they can be combined into one step or some steps can be split and decomposed into multiple steps. As long as they include the same logical relationship, they are all within the protection scope of this patent.

[0040] Definition of terms

[0041] As used herein, the term "porous styrene-divinylbenzene copolymer" or "SDB" refers to a porous skeleton structure formed by free radical polymerization, mainly using styrene as a monomer, divinylbenzene as a crosslinker, gasoline, liquid wax, solid wax, toluene, xylene, etc. as porogens. SDB has good chemical stability, highly cross-linked molecular structure and three-dimensional porous structure, and its pore size and specific surface area are relatively large. It is mainly used in environmental protection, pharmaceutical industry, chemical industry, analytical chemistry, clinical identification and other fields.

[0042] In the water hydrogen isotope exchange reaction, in order to avoid the active sites of the catalyst being covered by liquid water to cause "water poisoning", it is necessary to use an SDB carrier to provide hydrophobicity, but the hydrophobicity of SDB also hinders the improvement of the dispersibility of the active metal loaded on SDB by the impregnation reduction process. The smaller the active metal grains in the catalyst, the more catalytic active sites can be provided per unit active metal content, and the higher the catalytic activity of the catalyst. CN113019464A relates to a preparation method of a Pt / SDB hydrophobic catalyst, including roughening the SDB surface by physical etching of mechanical grinding and oxidative acid chemical etching, and then depositing Pt. The method utilizes two etching methods for SDB to provide more contact sites for the loading of active components. However, the average particle size of the prepared hydrophobic catalyst active metal grains is still large, the active metal inside the grains cannot fully play a role, the increase in catalytic activity is limited, and the waste of active metals is caused, and the two etchings can damage the mechanical strength of SDB. Therefore, it is of great significance to develop a highly active hydrophobic catalyst with a smaller active metal grain size and higher dispersion.

[0043] Based on this, the present application provides a hydrophobic catalyst and a preparation method thereof. The present application and optional implementation methods are described in more detail below.

[0044] Hydrophobic Catalyst

[0045] The present application provides a hydrophobic catalyst, comprising a porous styrene-divinylbenzene copolymer SDB and an active metal distributed on at least a portion of the surface of the SDB pore wall, wherein the active metal is selected from one or more of platinum, palladium, ruthenium, and rhodium, and the average particle size of the active metal grains is less than or equal to 4 nm.

[0046] In the SDB-based hydrophobic catalyst of the present disclosure, the active metal crystallites have a reduced average particle size, so that the active metal can provide increased catalytic active sites, thereby improving the catalytic activity of the catalyst.

[0047] According to some embodiments, the average particle size of the active metal grains is less than or equal to 4nm. Exemplarily, the average particle size of the active metal grains is 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm or a value between the ranges consisting of any two values, but not limited thereto. According to some embodiments, the average particle size of the active metal grains is 2nm to 3nm. As a result, it is more conducive to improving the utilization rate of the active metal by increasing the dispersibility of the active metal and increasing the activation sites.

[0048] The average particle size of the active metal grains can be measured by conventional methods. For example, a transmission electron microscope can be used to observe the active metal grains in the catalyst sample powder, and a number of active metal grains, such as more than 100 (such as 100 to 200), are randomly selected, and the distance between the two farthest points on the grain outline is used as the particle size to calculate the average particle size of the active metal grains. Software (such as Nano Measurer analysis software) can be used for auxiliary measurement.

[0049] According to some embodiments, the mass percentage of the active metal relative to the mass of the hydrophobic catalyst is 0.5% to 1.5%. Thus, it is more conducive to increasing the active metal loading and increasing the activation sites, thereby improving the utilization rate of the active metal. Exemplarily, the mass percentage of the active metal is 0.5%, 0.7%, 1%, 1.3%, 1.5% or a value between the ranges consisting of any two values, but is not limited thereto.

[0050] According to some embodiments, the hydrophobic catalyst further comprises a metal oxide distributed on at least a portion of the surface of the SDB pore wall, wherein the metal oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cobalt oxide, iron oxide, nickel oxide, and cerium oxide.

[0051] According to some embodiments, the mass percentage of the metal oxide is 0.2% to 0.7% relative to the mass of the hydrophobic catalyst. For example, the mass percentage of the metal oxide is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or a value between any two values, but not limited thereto.

[0052] Preparation method of hydrophobic catalyst

[0053] The present application also provides a method for preparing a hydrophobic catalyst, wherein the hydrophobic catalyst comprises a porous styrene-divinylbenzene copolymer SDB and an active metal distributed on at least a portion of the surface of the SDB pore wall, wherein the average particle size of the active metal grains in the hydrophobic catalyst is less than or equal to 4 nm, preferably 2 nm to 3 nm, wherein the method comprises: loading the metal oxide on the SDB by attaching a sol of the metal oxide to the SDB and then drying it to obtain a composite carrier; and loading the active metal on the composite carrier to obtain the hydrophobic catalyst, wherein the active metal is selected from one or more of platinum, palladium, ruthenium, and rhodium; and the metal oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cobalt oxide, iron oxide, nickel oxide, and cerium oxide.

[0054] The preparation method disclosed in the present invention first loads metal oxide onto the surface of the pores of SDB through sol, and when the active metal is subsequently loaded, the migration and aggregation of the active metal are inhibited through metal interaction, thereby facilitating the improvement of the dispersibility of the active metal subsequently loaded, increasing the active sites, and improving the catalytic exchange efficiency of the catalyst. Compared with the method of directly loading the active metal on SDB, the composite carrier disclosed in the present invention can make the distribution of the active metal more dispersed and uniform when the active metal is loaded, thereby facilitating the improvement of the utilization rate of the active metal and the improvement of the catalytic activity.

[0055] The present disclosure has no particular limitation on the source of the metal oxide sol, which can be obtained commercially, or can be prepared by a person skilled in the art according to a method known in the art. For example, the sol can be formed by using a metal alkoxide as a precursor, uniformly mixing it in water or an organic solvent, and performing a hydrolysis and condensation chemical reaction.

[0056] According to some embodiments, the sol of the metal oxide is prepared on-site, and the preparation method includes hydrolyzing the metal alkoxide in an acidic aqueous solution. Exemplarily, the sol of titanium oxide can be obtained by hydrolyzing tetrabutyl titanate under acidic conditions. Exemplarily, the pH of the acidic aqueous solution is 1, 2, 3, 4, 5, 6 or a value between the ranges consisting of any two values, but is not limited thereto. Preferably, the pH of the acidic aqueous solution is 1 to 2. Thus, it is conducive to the rapid formation of the metal oxide sol. Preferably, the acidic aqueous solution is an aqueous solution of hydrofluoric acid.

[0057] According to some embodiments, in the sol, the content of the metal oxide is 0.5% to 1.5% by mass. This content range is conducive to the stability of the sol, thereby improving the dispersibility of the metal oxide in the composite support. Exemplarily, the content of the metal oxide is 0.5%, 0.7%, 1.0%, 1.2%, 1.5% or a value between the ranges consisting of any two values, but is not limited thereto.

[0058] According to some embodiments, the SDB comprises one or more of the following features: the BET specific surface area of ​​the SDB is 35 m 2 / g to 45m 2 / g, and / or the average pore size of the SDB is 140nm to 180nm, and / or the pore volume of the SDB is 1.4cm 3 / g to 1.8cm 3 / g. This is beneficial to increase the growth sites of active metals.

[0059] The present disclosure has no particular limitation on the method for attaching the metal oxide sol to SDB, which can be achieved by mechanical dispersion, such as impregnation, high-speed stirring, ultrasonic dispersion, etc. Preferably, the method comprises mixing SDB with the metal oxide sol and then ultrasonically dispersing for 10 to 20 minutes. This is conducive to more uniform dispersion of the metal oxide on the SDB carrier.

[0060] According to some embodiments, the metal oxide sol is attached to the SDB and then dried at a temperature of 50° C. to 70° C. This is conducive to the metal oxide sol being more stably attached to the SDB. Exemplarily, the drying temperature is 50° C., 55° C., 60° C., 65° C., 70° C., or a value between any two values, but is not limited thereto.

[0061] According to some embodiments, the mass ratio of the composite carrier to the SDB is (1.02-1.08): 1. Exemplarily, the mass ratio of the composite carrier to the SDB is 1.02: 1, 1.03: 1, 1.04: 1, 1.05: 1, 1.06: 1, 1.07: 1, 1.08: 1 or a value between any two values, but is not limited thereto.

[0062] According to some embodiments, loading the active metal onto the composite support includes impregnating the composite support with a solution containing ions of the active metal element and then drying to obtain a reduced precursor; and performing a reduction treatment on the reduced precursor to obtain the hydrophobic catalyst, wherein the reduction treatment includes reducing the reduced precursor in an atmosphere containing a reducing gas. The above-mentioned impregnation utilizes a uniform solution containing ions of the active metal element, thereby improving the dispersibility of the active metal. The above-mentioned reduction process is conducive to the full reduction of the salt of the active metal.

[0063] According to some embodiments, the solvent of the solution is selected from one or more of ethanol, methanol, water, and ethylene glycol, thereby facilitating the solution to diffuse smoothly into the interior of the carrier.

[0064] According to some embodiments, the content of the active metal element in the solution is 1 g / L to 5 g / L. Exemplarily, the content of the active metal element in the solution is 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L or a value between any two values, but not limited thereto. This is conducive to more uniform dispersion of the active component on the carrier.

[0065] According to some embodiments, the reducing gas is hydrogen, and the reduction temperature is 280°C to 320°C. For example, the content of active metal elements in the solution is 280°C, 290°C, 300°C, 310°C, 320°C, or a range between any two values, but not limited thereto. This is conducive to the full reduction of active components.

[0066] According to some embodiments, after the active metal is loaded onto the composite support, the preparation method further comprises etching at least a portion of the metal oxide with an alkaline solution. The active metal and SDB are stable relative to the alkaline solution, and the alkaline solution selectively etches and removes a portion of the metal oxide, increasing the exposed area of ​​the SDB, improving the hydrophobicity, and thus improving the catalytic exchange efficiency of the hydrophobic catalyst.

[0067] According to some embodiments, the alkali in the alkaline solution is selected from one or more of NaOH, KOH, and ammonia water, thereby being conducive to etching away most of the metal oxides while avoiding damage to the active metals that have been loaded.

[0068] According to some embodiments, the mass percentage of the alkali in the alkali solution is 1 wt% to 3 wt%. Exemplarily, the mass percentage of the alkali in the alkali solution is 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt% or a value between any two values, but not limited thereto.

[0069] According to some embodiments, the solvent of the alkaline solution is selected from one or more of ethanol, methanol, and ethylene glycol.

[0070] According to some embodiments, the ratio of the volume of the alkaline solution to the mass of the hydrophobic catalyst is 3.5 mL / g to 4.5 mL / g. Exemplarily, the ratio of the volume of the alkaline solution to the mass of the hydrophobic catalyst is 3.5 mL / g, 3.7 mL / g, 4 mL / g, 4.2 mL / g, 4.5 mL / g, or a value between any two values, but not limited thereto. Thus, it is beneficial to fully etch the metal oxide.

[0071] According to some embodiments, the etching time is 0.5h to 1.5h. For example, the etching time is 0.5h, 0.7h, 1.0h, 1.2h, 1.5h or a value between any two values, but not limited thereto. Thus, it is more conducive to fully etching the metal oxide without affecting the active metal content.

[0072] Example

[0073] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0074] Example 1

[0075] Preparation of metal oxide sols

[0076] 0.5 mL of HF solution (Beijing Beihua Fine Chemicals Co., Ltd., analytical grade) and 2 mL of deionized water were added to 11 mL of ethanol and stirred for 5 minutes using a magnetic stirrer. Then 0.5 mL of tetrabutyl titanate was slowly added dropwise while stirring for 30 minutes to obtain a TiO2 sol. In the sol, the content of TiO2 was 1.2% by mass.

[0077] Preparation of composite carrier

[0078] 2.242 g of SDB (ADS-5 type from Tianjin Nankai Hecheng Technology Co., Ltd., with a specific surface area of ​​40.112 m 2 / g, the average pore diameter is 158.06nm, and the pore volume is 1.5850cm 3 / g) was poured into the above TiO2 sol, stirred and ultrasonically dispersed for 10 minutes. Then, it was dried in an oven at 60°C for 5 hours to obtain 2.323g of the composite carrier. The mass ratio of the composite carrier to SDB was 1.04:1.

[0079] Loading active metals

[0080] 2.323g composite carrier is impregnated in the ethanol solution (wherein the content of platinum element is 2.3g / L) of 10mL hexahydrate chloroplatinic acid.After ethanol is completely volatilized, put into baking oven and dry 60 ℃ for 24 hours.Dried sample is placed in tubular reduction furnace, under N2 (flow is 500mL / min) atmosphere, rise to 250 ℃ by room temperature with the speed of 10 ℃ / min, after reaching this temperature, pass into H2 (flow is 500mL / min) and reduce, at 250 ℃ of temperature, reduce 10 hours, stop passing into H2 after reduction terminates, under N2 (flow is 500mL / min) protection, cool overnight, obtain 2.347g hydrophobic catalyst, wherein relative to the quality of described hydrophobic catalyst, the mass percentage of active metal is 1.02wt%.

[0081] Morphology of hydrophobic catalysts

[0082] The above hydrophobic catalyst was ground in a mortar to obtain a sample powder.

[0083] The sample powders were observed by transmission electron microscopy (TEM, JEOL JEM-F200, Japan). Figure 1 As shown, 120 catalyst active component Pt grains were randomly selected, and the average particle size of the Pt grains was calculated using Nano Measurer analysis software.

[0084] Catalytic exchange efficiency test

[0085] The catalytic activity of the hydrophobic catalyst of Example 1 was tested using a parallel-flow hydrogen isotope liquid-phase catalytic exchange device. Before the catalytic reaction began, constant-temperature water at 60°C was introduced into the device to preheat the catalytic column (equipped with 5 mL of the above-mentioned hydrophobic catalyst) and the packing column, and then the air in the N2 purge device was introduced. H2 was introduced from the bottom of the water vapor saturator at a volume flow rate of 4.23L / min, and saturated light and heavy water vapor at a temperature of 60°C was brought into the catalytic column. The deuterium abundance of the gas sample at the inlet and outlet of the catalytic column was measured using a mass spectrometer (Thermofisher, MAT253). The deuterium density of the water sample was measured using a densitometer for the gas condensate after the reaction.

[0086] The catalytic exchange efficiency η was calculated by the following formula.

[0087]

[0088] Where X represents the percentage of deuterium atoms in the gas condensate after the isotope exchange reaction; Y0 represents the percentage of deuterium atoms at the inlet of the catalytic column, and Y t It represents the percentage of deuterium atoms at the outlet of the catalytic column; Y* is the percentage of deuterium atoms in the inlet and outlet gases of the catalytic column when equilibrium is reached; α represents the separation coefficient of hydrogen-deuterium phase exchange, and α is 1.046 at 60°C.

[0089] Example 2

[0090] The hydrophobic catalyst was prepared in the same manner as in Example 1, except that after reduction and cooling, 2.347 g of the sample was placed in 10 mL of 2 wt% sodium hydroxide ethanol solution for etching for 1 h, then washed with deionized water 5 times, and dried at 60 ° C for 5 h to obtain 2.276 g of a hydrophobic catalyst having a morphology as shown in FIG. Figure 2 shown.

[0091] Comparative Example 1

[0092] The hydrophobic catalyst was prepared in the same manner as in Example 1, except that 2.242 g of SDB was used instead of the composite carrier, and Pt was directly loaded onto SDB to obtain a hydrophobic catalyst having a morphology as shown in FIG. Figure 3 shown.

[0093] Comparative Example 2

[0094] A hydrophobic catalyst was prepared in the same manner as in Example 1, except that after reduction cooling, 2.347 g of the sample was placed in 10 mL of a 0.4 wt % HF aqueous solution and etched for 1 h, then washed 5 times with deionized water, and dried at 60° C. for 5 h to obtain a hydrophobic catalyst.

[0095] The average particle size and catalytic exchange efficiency of the Pt crystals of the hydrophobic catalysts prepared in Examples 1-2 and Comparative Examples 1-2 are shown in Table 1 below.

[0096] Table 1

[0097]

[0098]

[0099] Among them, “ / ” means that no corresponding performance test data is made.

[0100] The above results show that the present invention inhibits the migration and aggregation of Pt in the subsequent Pt loading process by first attaching the metal oxide TiO2 to SDB, thereby improving the Pt dispersion. Compared with Example 1, Example 2 further improves the catalytic exchange efficiency through the alkaline solution etching disclosed in the present invention.

[0101] The above descriptions are only some specific embodiments of the present disclosure, which are intended to illustrate the present disclosure and are not intended to limit the scope of protection claimed in the present application. All modifications, substitutions, or direct / indirect applications made in other related technical fields based on the inventive concept of the present disclosure and using the description of the present application are included in the scope of protection claimed in the present application.

Claims

1. A hydrophobic catalyst comprising a porous styrene-divinylbenzene copolymer (SDB) and an active metal distributed on at least a portion of the surface of the pore wall of the SDB, wherein: The active metal is selected from one or more of platinum, palladium, ruthenium and rhodium, and the average particle size of the active metal crystal grains is less than or equal to 4 nm.

2. The hydrophobic catalyst according to claim 1, characterized in that The average particle size of the active metal crystal particles is 2 nm to 3 nm; preferably, the mass percentage of the active metal relative to the mass of the hydrophobic catalyst is 0.5% to 1.5%.

3. The hydrophobic catalyst according to claim 1, characterized in that The hydrophobic catalyst also includes a metal oxide distributed on at least a portion of the surface of the SDB pore wall, wherein the metal oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cobalt oxide, iron oxide, nickel oxide, and cerium oxide; preferably, the mass percentage of the metal oxide relative to the mass of the hydrophobic catalyst is 0.2% to 0.7%.

4. A method for preparing a hydrophobic catalyst, characterized in that: The hydrophobic catalyst comprises a porous styrene-divinylbenzene copolymer SDB and an active metal distributed on at least a portion of the surface of the SDB pore wall, wherein the average particle size of the active metal crystals in the hydrophobic catalyst is less than or equal to 4 nm, preferably 2 nm to 3 nm, wherein the method comprises: The metal oxide is loaded on the SDB by attaching a sol of the metal oxide to the SDB and then drying the sol to obtain a composite carrier; and The active metal is loaded onto the composite carrier to obtain the hydrophobic catalyst, Wherein, the active metal is selected from one or more of platinum, palladium, ruthenium and rhodium; the metal oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cobalt oxide, iron oxide, nickel oxide and cerium oxide.

5. The preparation method according to claim 4, characterized in that: In the sol, the content of the metal oxide is 0.5% to 1.5% by mass.

6. The preparation method according to claim 4, characterized in that: The drying temperature is 50°C to 70°C; preferably, the mass ratio of the composite carrier to the SDB is (1.02 to 1.08):

1.

7. The preparation method according to claim 4, characterized in that: The SDB includes one or more of the following features: (1) The BET specific surface area of ​​the SDB is 35 m 2 / g to 45m 2 / g, (2) The average pore size of the SDB is 140 nm to 180 nm, (3) The pore volume of the SDB is 1.4 cm 3 / g to 1.8cm 3 / g.

8. The preparation method according to claim 4, characterized in that: Loading the active metal onto the composite support comprises: Impregnating the composite support with a solution containing ions of the active metal element and then drying to obtain a reduced precursor, preferably, the solvent of the solution is selected from one or more of ethanol, methanol, water, and ethylene glycol, and preferably, the content of the active metal element in the solution is 1 g / L to 5 g / L; and The reduction precursor is subjected to a reduction treatment to obtain the hydrophobic catalyst, wherein the reduction treatment includes reducing the reduction precursor in an atmosphere containing a reducing gas; preferably, the reducing gas is hydrogen, and the reduction temperature is 280°C to 320°C.

9. The preparation method according to claim 4, characterized in that: After the active metal is loaded onto the composite support, the preparation method further comprises etching at least a portion of the metal oxide with an alkaline solution.

10. The preparation method according to claim 9, characterized in that: The alkali in the alkaline solution is selected from one or more of NaOH, KOH, and ammonia water; preferably, the mass percentage of the alkali in the alkaline solution is 1wt% to 3wt%; preferably, the solvent of the alkaline solution is selected from one or more of ethanol, methanol, and ethylene glycol; preferably, the ratio of the volume of the alkaline solution to the mass of the hydrophobic catalyst is 3.5mL / g to 4.5mL / g; preferably, the etching time is 0.5h to 1.5h.

Citation Information

Patent Citations

  • Preparation method of size-controllable spherical SDB hydrophobic carrier and Pt / SDB hydrophobic catalyst

    CN113019464A

  • Hydrophobic catalyst for producing methyl methacrylate with one-step oxidative esterification and preparation method of hydrophobic catalyst

    CN103721744A

  • Flexible platinum formaldehyde room-temperature oxidation catalyst and preparation method thereof

    CN106807451A

  • Preparation method of nano ferroferric oxide doped styrene-divinylbenzene copolymer hydrophobic catalyst carrier

    CN107973872A

  • Catalyst for catalyzing selective hydrogenation of chloro nitro-compound

    CN107999116A